A CRITICAL EXAMINATION OF THE ENGLISH TEACHING MODULE CRAFTED FOR THE INDEPENDENT CURRICULUM BY TEACHERS AT MOJOKERTO JUNIOR HIGH SCHOOL - Devinta Nirmalasari; Rini Lindawati; Wiwik Mardiana (International Journal of Teaching and Learning, 2025)
This study aims to explore the unique curriculum instruction modules used by English teachers in five Movement Schools in Mojokerto junior high schools. A qualitative approach with a case study method was employed to examine how these modules are implemented. Data were collected through interviews with educators, analysis of relevant documents, and a review of the teaching module. The findings reveal that the five English teachers at these schools have structured their Teaching Modules in line with the components of the Independent Curriculum. However, they still face difficulties developing these modules and adapting the curriculum to meet students' needs. The study emphasizes that teaching modules should be designed to consider both the specific needs of local students and the national education guidelines. These findings significantly affect how secondary school teachers plan and develop instructional strategies.